(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the modern education system, the acquisition of the necessary skills in subjects through practical and laboratory work, the concept of a virtual laboratory, the main advantages of creating virtual laboratory, the issue of using virtual laboratories in pedagogical activities.